2021
DOI: 10.18805/ijar.b-4295
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Characterization of Riemerella anatipestifer from Domesticated Ducks of Assam, India

Abstract: Background: Riemerella anatipestifer (R. anatipestifer) is a gram negative, microaerophilic, non-motile, bipolar bacteria. High genetic diversity and molecular differentiation were reported among field isolates. Although the bacterium causes one of the most economically important duck diseases in the north-eastern region of India, little work has been done on isolation, identification and molecular characterization of the bacteria. Hence, the present investigation was undertaken with a view to characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(41 reference statements)
2
3
0
Order By: Relevance
“…The maximum morbidity and mortality was observed during June to July at the 8-10 weeks of age group by(Sarker et al 2017) whereas the outbreak was also reported during summer(Haque 1987). The mortality rate in ducklings were higher than adult ducks which in agreement with(Doley et al 2003). The survey revealed both the morbidity and mortality were 75-80% and 40-45% on the basis of farmer's history.…”
supporting
confidence: 78%
“…The maximum morbidity and mortality was observed during June to July at the 8-10 weeks of age group by(Sarker et al 2017) whereas the outbreak was also reported during summer(Haque 1987). The mortality rate in ducklings were higher than adult ducks which in agreement with(Doley et al 2003). The survey revealed both the morbidity and mortality were 75-80% and 40-45% on the basis of farmer's history.…”
supporting
confidence: 78%
“…The maximum morbidity and mortality were observed during June to July at the 8–10 weeks of age group by Sarker et al [ 6 ], whereas the outbreak was also reported during the summer [ 22 ]. The mortality rate in ducklings was higher than that in adult ducks, which agrees with Doley et al [ 30 ]. Based on the farmer’s history, the survey found that morbidity and mortality were 75%–80% and 40%–45%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Riemerella anatipestifer is an important infectious disease that impacts commercial poultry production globally. A large number of case reports of RA infections in poultry are from Asia and mainly concern the duck industry [ 6 , 24 , 25 , 26 , 27 ]. It can be observed, however, that the number of papers describing RA infections in Europe has increased in the last decade.…”
Section: Discussionmentioning
confidence: 99%